The Influence of Ad Appeal and Competitive Pricing on Purchase Decisions with Consumer Buying Interest As An Intervening Variable in Indomie Consumers - Armada Armada; Henny Welsa; Nonik Kusuma Ningrum (Green Publisher Indonesia, 2025)
This research aims to find out how much influence Advertising Attractiveness (DTI), Competitive Prices (HK) and Consumer Purchase Interest (MBK) have on Purchasing Decisions (KP) for Indomie Products. The population used in this research is consumers who have accessed the Shopee application. The sample in this study was 100 respondents using the Non-Probability Sampling technique with a purposive sampling approach (sampling based on certain criteria, with the criteria being that respondents had purchased Indomie after seeing the advertisement. Data was taken using a questionnaire via Google Form, after the questionnaire results were collected then Data was tabulated using MS Excel and analyzed using SPSS version 29. The results of this research show that advertising attractiveness has an effect on consumer buying interest, competitive prices (HK) have a significant effect on consumer buying interest (MBK), consumer buying interest (MBK) has a positive and significant effect on purchasing decisions (KP) Influence of advertising attractiveness (DTI) on Purchasing Decisions (KP) through Consumer Purchase Intentions (MBK) as an accepted intervening variable. The influence of Competitive Prices on Purchasing Decisions (KP) through Consumer Purchase Interest (MBK) as an accepted intervening variable